2013
DOI: 10.1093/toxsci/kft019
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Analysis of Multiwalled Carbon Nanotube-Induced Cellular Signaling and Gene Expression in Human Small Airway Epithelial Cells

Abstract: Multiwalled carbon nanotubes (MWCNT) are one of the most commonly produced nanomaterials, and pulmonary exposure during production, use, and disposal is a concern for the developing nanotechnology field. The airway epithelium is the first line of defense against inhaled particles. In a mouse model, MWCNT were reported to reach the alveolar space of the lung after in vivo exposure, penetrate the epithelial lining, and result in inflammation and progressive fibrosis. This study sought to determine the cellular a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(52 citation statements)
references
References 33 publications
1
51
0
Order By: Relevance
“…A model consisting of macrophages and A549 cells in the upper chamber and dendritic cells on the basal side of the membrane in the lower chamber showed substantial inflammatory signaling induced by MWCNT exposure (Gasser et al, 2012). It has also been shown that 1.2 mg/ml MWCNT exposure to small airway epithelial cells resulted in elevated expression of genes related to inflammation and release of inflammatory cytokines (Snyder-Talkington et al, 2013b) and also on activated human microvascular endothelial cells in the lower chamber of a co-culture system (Snyder-Talkington et al, 2013a). Therefore, small airway epithelial cells could be more capable of releasing inflammatory mediators than A549 cells, although the latter do respond with increased IL-6 and IL8 transcription at very high exposure concentrations of, e.g., diesel exhaust particles (Dybdahl et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…A model consisting of macrophages and A549 cells in the upper chamber and dendritic cells on the basal side of the membrane in the lower chamber showed substantial inflammatory signaling induced by MWCNT exposure (Gasser et al, 2012). It has also been shown that 1.2 mg/ml MWCNT exposure to small airway epithelial cells resulted in elevated expression of genes related to inflammation and release of inflammatory cytokines (Snyder-Talkington et al, 2013b) and also on activated human microvascular endothelial cells in the lower chamber of a co-culture system (Snyder-Talkington et al, 2013a). Therefore, small airway epithelial cells could be more capable of releasing inflammatory mediators than A549 cells, although the latter do respond with increased IL-6 and IL8 transcription at very high exposure concentrations of, e.g., diesel exhaust particles (Dybdahl et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Six biological replicates of each SAEC and HMVEC monoculture exposure condition were collected for microarray analysis. Both SAEC and HMVEC in monoculture have been shown to interact with MWCNT (Pacurari et al 2012; Snyder-Talkington et al 2013b). …”
Section: Methodsmentioning
confidence: 99%
“…These findings show that MWCNT-7 exposure engages cells to control their DNA integrity and growth, and that cell growth may be activated by the overexpression of genes that activate growth and the underexpression of genes which normally exert a negative control. Snyder-Talkington et al (2013b) reported alterations of genes associated to cellular growth and proliferation in telomerase immortalized-human small airway epithelial cells (SAEC) after in vitro exposure to MWCNT-7. Several of these genes, were upregulated such as V-Akt murine thymoma viral oncogene homolog 1 ( AKT1 ), which is activated by growth factors; vascular endothelial growth factor A ( VEGFA ); smoothened, frizzled class receptor ( SMO ) and Sonic Hedgehog ( SHH ), involved in hedgehog signaling and carcinogenesis; as well as downregulation of B-cell CLL/lymphoma 2 ( BCL2 ), an apoptosis inhibitor.…”
Section: Genotoxicitymentioning
confidence: 99%
“…This may suggest a growth advantage of MWCNTs-exposed SAEC. Moreover, these genes have a role in lung adenocarcinoma (Snyder-Talkington et al (2013b). Early passage immortalized cells are used in these studies to analyze genetic changes in a cell population in response to a toxic agent; these results are reliable because early passage immortalized cells have a stable genotype.…”
Section: Genotoxicitymentioning
confidence: 99%